Night Market Escape in VR - A Hamid, Rahayu; Aziz, Mohd Nor Azizie (Applied Information Technology And Computer Science, 2020)
Maze is a puzzle with network of paths or passage which one has to find a way. Maze game nowadays not provide a real life situation and player cannot fully experience real adventure that maze game can provide. Maze game nowadays need a gameplay that allow player to roam around the maze world and admire breath taking views through a virtual world while solving the maze. Night Market Escape in VR game was developed to provide virtual reality maze game with enjoyable first person view experience. This game was develop using the Game Development Life Cycle (GDLC) methodology. The GDLC consist of six phase which is Initiation phase, Pre-Production phase, Production Phase, Testing phase, Beta phase and Release Phase. All the phase will be used to develop the game except the release phase. At the end of this project, maze game can be played in the virtual world with the Malaysia night market environment. This game will provide enjoyable experience for user and can promote Malaysia to the world as this game are using Malaysia Night Market Environment.